Theoretical and methodological principles of formation the professional culture of future lawyers - Макеєва, О. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article defines the nature and structure of the professional culture of lawyers, main forms andmethods of education of future lawyers. The author concludes, that only complex approach at the educationalwork will form a highly professional specialist in the field of jurisprudence.